Correlation analysis of exercise volume and musculoskeletal disorders in people with income level differences: research based on the 2011–2018 NHANES dataset - Xiangjun Pan; Shibo Liu; Bo Chen; Zehao Yu; Wang Hao; Xiongfeng Tang; Yanguo Qin (BMC Public Health)
Abstract Objectives Socioeconomic factors significantly impact human health; however, the impact of exercise and income on musculoskeletal system health remains unclear. Our study aims to explore the relationship between exercise and income with musculoskeletal system health in young and middle-aged adults. Design This cross-sectional study used data from 7,515 adults aged 20–59 years, which were obtained from the US NHANES, 2011–2018. Participants’ musculoskeletal system health was evaluated on the basis of them having osteopenia, osteoporosis, or sarcopenia. Methods Ordinal regression was used to explore the correlation between income level, exercise volume, and musculoskeletal system health. Mediating effect analysis was used to assess whether the exercise volume affected the impact of income levels on musculoskeletal system health. Ordinal regression and restricted cubic spline curve were used to further analyze the relationship between exercise and income level. Results In the analysis of adjusted all covariates, the probability of having good musculoskeletal system health in high-income participants was higher than that of low- or middle-income participants. The probability of having good musculoskeletal system health in the actively exercising group higher than that of the participants exercised insufficiently or sufficiently. Mediating effect of exercise masked the effect of income on musculoskeletal system health. Participants with low income levels tended to spend more time exercising that those who had high income levels; exercise volume and income level had a significant non-linear relationship. Conclusion The findings presented will help identify young and middle-aged adults who are most at risk of developing musculoskeletal health problem and will likely benefit from certain lifestyle interventions.